2020
DOI: 10.3390/w12020580
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Water Sources in a Coastal Gold Mine through an End-Member Mixing Analysis Combining Multivariate Statistical Methods

Abstract: Mixing calculations have been widely applied to identify sources of groundwater recharge, but these calculations have assumed that the concentrations of end-members are well known. However, the end-members of water remain unclear and are not easily available in practical applications. To better determine end-members and mixing ratios, an end-member mixing analysis combining multivariate statistical methods was used on a large, complex water chemistry dataset collected from the Shashandao gold mine in China. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The alteration zone has been obviously zoned through multi-stage tectonic movement, and it basically spreads along the tendency and strike of fault F1. The gold deposits mainly occur in the cataclastic rocks within 40 m of fault F1, and they mainly consist of veined and reticulated mineralized rocks [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Geological Environment and Engineering Propertiesmentioning
confidence: 99%
“…The alteration zone has been obviously zoned through multi-stage tectonic movement, and it basically spreads along the tendency and strike of fault F1. The gold deposits mainly occur in the cataclastic rocks within 40 m of fault F1, and they mainly consist of veined and reticulated mineralized rocks [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Geological Environment and Engineering Propertiesmentioning
confidence: 99%
“…PCA is a basic multivariate statistical analysis method. Its main idea is to construct a linear combination of raw variables and compress multiple groups of complex variables into simple comprehensive variables to achieve the effects of compressing data and extracting main information [20][21][22][23][24]. In order to avoid the influence of different data units on the calculation results, the raw data was standardized by z-scores firstly, n samples were x i = ðx i1 , x i2 , ⋯, x ip Þ, and the formula was as follows [25,26]: 4 Geofluids Z ij is the standardized data, and x j and s 2 j are the mean and variance of j column elements of the raw data, respectively.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Literature studies covered the application of HCA for hydro-geochemical characteristics and groundwater quality evaluation/classification based on sampled data. For example, Chai et al and Liu et al suggested that HCA is a powerful tool for evaluating groundwater pollution and identifying groundwater hydro-geochemical characteristics in China [18,19]. Similarly, HCA has been used for groundwater classification in Southern Ghana [20]; water quality assessment in East Algeria [21]; hydro-geochemical analysis of groundwater in Iran [22] to name a few.…”
Section: Introductionmentioning
confidence: 99%